Analilis Pendekatan Metode Vector Autoregressive (VAR) dalam Meramalkan Jumlah Pengadaan Beras di Sulawesi Selatan - Yulia, Yulia Novita Sari; Adnan Sauddin; Khalilah Nurfadilah (Jurnal MSA (Matematika dan Statistika serta Aplikasinya), 2024)
This study discusses forecasting the amount of rice procurement in South Sulawesi. The need increases every year because it is one of the staple foods of the Indonesian population that is consumed everyday. Related to this, to ensure the availability of stock of rice suppiles throughout the South Sulawesi region, this is done by estimating the number of procurements in terms of rice prices and rice production. The purpose of this study is to determine the forecasting model, the variables that have a relationship between variables and the results of forecasting the amount of rice procurement. The results obtained in this study indicate that the smallest AIC value is found in the length of lag 2 so that the model used is the VAR model (3). In addition, all the variables used have a significant effect. Then from the forecasting results obtained, the rice price variabes (Y1) and the amount of rice production (Y2) have MAPE values of 20,4 % dan 14,0 %, which means the forecasting results are good. The results of the forecast number of procurement based on the price in term of the price of rice and the amount of production in the text five years has increased every year.